Gallic Acid Alleviates Psoriasis Keratinization and Inflammation by Regulating BRD4 Expression - Zhang, Li; Ye, Qiaoyuan; Gan, Saiyang; Liu, Huan; Zhang, Qing; Wang, Shuangshuang; Cheng, Can (Folia biologica, 2024)
Psoriasis is a chronic non-contagious autoimmune disease. Gallic acid is a natural compound with potential health benefits, including antioxidant, anticancer, antiviral and antibacterial properties. Nevertheless, the influence of gallic acid on psoriasis has not been fully determined. This investigation aimed to discover the effect of gallic acid on psoriasis. Thirty-one pairs of psoriatic skin tissues and healthy adult human skin tissues were collected. Human keratinocytes (HaCaT cells) were transfected with interleukin 17A (IL-17A) to create the psoriatic keratinocyte model. The content of bromodomain-containing protein 4 (BRD4) microRNA was assessed using qRT-PCR testing. The content of BRD4 was detected by Western blotting. Cell migration was evaluated by conducting a wound healing assay. Cell proliferation was determined using an EdU assay. Apoptosis was detected by the TUNEL assay. The contents of interferon gamma (IFN-γ), IL-6, IL-8 and IL-17 were detected by ELISA. BRD4 was up-regulated in psoriatic skin tissues and in the IL-17A group compared to the healthy adult human skin tissues and the control group. Silencing BRD4 inhibited cell migration, proliferation and inflammatory response but induced apoptosis in IL-17A-treated HaCaT cells. Conversely, BRD4 over-expression promoted cell migration, proliferation and inflammatory response but suppressed apoptosis in IL-17A-treated HaCaT cells. Gallic acid repressed cell migration, proliferation and inflammatory response but indu-ced apoptosis in HaCaT cells transfected with IL-17A by down-regulating BRD4. Gallic acid represses cell migration, proliferation and inflammatory response but induces apoptosis in IL-17A-transfected HaCaT cells by down-regulating BRD4.
Keywords: Cell Line; jaderné proteiny; keratinocyty; Cell Movement; apoptóza; Keratinocytes; Inflammation; Nuclear Proteins; Interleukin-17; mikro RNA; Gene Expression Regulation; zánět; mužské pohlaví; Cell Proliferation; Adult; Gallic Acid; Transcription Factors; Psoriasis; MicroRNAs; buněčné linie keratinocytů HaCaT; Cell Cycle Proteins; regulace genové exprese; transkripční faktory; proteiny buněčného cyklu; ženské pohlaví; Humans; pohyb buněk; proteiny obsahující bromodoménu; HaCaT Cells; Bromodomain Containing Proteins; interleukin-17; kyselina gallová; proliferace buněk; buněčné linie; dospělí; Female; lidé; Male; Apoptosis; psoriáza